Three-Phase Partitioning for the Extraction and Purification of Polysaccharides from the Immunomodulatory Medicinal Mushroom Inonotus obliquus - Zhendong Liu; Dongsheng Yu; Liang Li; Xiaoxiao Liu; Henan Zhang; Wenbo Sun; Chi-Chung Lin; Jiafu Chen; Zhi Chen; Wenhan Wang; Wei Jia (Molecules, 2019)
Polysaccharides from the immunomodulatory medicinal mushroom Inonotus obliquus (IOPS) were extracted and purified using three-phase partitioning (TPP), which is an efficient, fast, safe, and green purification technique. An optimal extraction procedure that gave a good 2.2% isolated yield was identified, using the following protocol: a solid-liquid ratio of 1 g to 12 mL; mass fraction of (NH4)2SO4 20% (w/v); 11 mL t-butanol; pH 8.0; temperature 30 °C; and extraction time 30 min. The purified IOPS was shown to be a proteoglycan of 40 kDa molecular weight comprising of d-galactose, d-glucose, d-xylose, and d-mannose in a molar ratio of 2.0:3.5:1.0:1.5. The purified IOPS displayed strong free-radical scavenging abilities, antioxidant activities, and immunological activity in vitro. IOPS’ Trolox antioxidant equivalent capacity and ferric-reducing ability of plasma were 251.2 μmol Trolox/g sample and 1040.5 μmol Fe2+/g sample, respectively, with the activity of its immunomodulatory behavior shown to be gradient dependent.